Integrating oxidative-stress biomarkers into a precision oncology risk-stratification model for bladder cancer prognosis and therapy - Huang, Jianxu; Zhou, Dewang; Luo, Weihan; Liu, Yujun; Zheng, Haoxiang; Wang, Yongqiang (Frontiers in Cell and Developmental Biology, 2024)
Bladder cancer is one of the most prevalent malignant tumors, characterized by its heterogeneous nature. This heterogeneity requires the implementation of a strict, stratified strategy to optimize clinical decision-making processes and enhance patient counseling. In this study, a prognostic model based on oxidative stress-related genes was established for risk stratification in bladder cancer. Firstly, differentially expressed oxidative stress-genes were identified using GEO databases, and functional enrichment and survival analyses were performed on the screened genes. Following this, a risk-scoring model was constructed and evaluated for its efficacy in prognostic prediction, subtyping, and therapeutic responses in bladder cancer, while a predictive model for clinical application was also created. Moreover, samples from two muscle-invasive and two non-muscle-invasive bladder cancer patients were analyzed, and the expression of candidate genes was validated using quantitative real-time PCR (qRT-PCR). This study provided a new risk stratification model that can serve as a reliable reference for prognosis and personalized therapeutic strategies in bladder cancer patients.